Science Teachers’ Argument Types and Supporting Reasons on Socioscientific Issues: COVID-19 Pandemic - Atabey, Nejla (BILGE AKADEMIK YAYINCILIK EGITIM BILISIM VE DANISMANLIK HIZMETLERI, 2021)
This study examines the types of arguments and supporting reasons of science teachers on socioscientific issues. The case study was used in this study conducted with seven science teachers. Data were collected through three scenarios developed about vaccination, curfew and distance education in the context of COVID-19. Within the context of the data obtained, the argument types of the teachers were evaluated through the deductive content analysis, and the supporting reasons they presented for their arguments were evaluated through the inductive content analysis. Study results showed that the science teachers offered more arguments, including a claim and the reasons supporting this claim and that the arguments where the pros and cons analysis was performed and the reasons for the different aspects of an issue are presented in detail could be presented less. In addition, although there were differences in the supporting reasons of the teachers according to the content of the scenario, these reasons were concentrated on the subject areas of health, social, value and personal experience. The findings can contribute to improving the science teachers’ argumentation qualifications and increasing the quality of in-class argumentation practices.
Keywords: Other Fields of Education; Alan Egitimleri